Conscious capitalism : Liberating the heroic spirit of business / John Mackey, Rajendra Sisodia ; Foreword: Bill George - Mackey, John
John Mackey and Raj Sisodia's iconic book, Conscious Capitalism, introduced business leaders to a set of core principles--higher purpose, stakeholder integration, conscious leadership, and conscious culture--that are being widely adopted by leading companies around the world and transforming how they do business. Now, a "field guide" codifies these best practices, with a systematic process and proven tools for sharing and implementing the four core principles throughout the organization. This practical guide provides hands-on materials--exercises, assessments, and checklists--used to implement the tenets of conscious capitalism and build conscious leadership in companies such as Whole Foods Market, Southwest Airlines, Life is Good, The Container Store, Barry-Wehmiller, Zappos, and many others. Organized according to each of the four core principles, chapters provide exercises, worksheets, and instructions--for use both individually and with teams--as well as advice, examples, and real-life stories to help leaders apply these ideas and make them come alive in their organizations. This is the authoritative resource for practicing higher purpose, stakeholder orientation, conscious culture, and conscious leadership--and becoming a more conscious organization